An Unusual Association in an Uncommon Disease: Two Cases of Spontaneous Pneumomediastinum Associated with Pneumorrhachis - Luís Martins; Patrícia Dionísio; Susana Moreira; Alda Manique; Isabel Correia; Cristina Bárbara (Case Reports in Pulmonology)
Pneumomediastinum, the presence of free air in the mediastinum, is described as spontaneous pneumomediastinum when there is no apparent cause such as trauma, surgery, interventional procedures, or intrathoracic infections. Pneumorrhachis is a rare clinical condition, consisting of intraspinal air. The main causes are iatrogenic, traumatic, and nontraumatic. Spontaneous mediastinum is usually associated with subcutaneous emphysema and, occasionally, with pneumothorax; however, its association with pneumorrhachis is extremely rare. Here, we present two rare cases of spontaneous pneumomediastinum associated with pneumorrhachis caused by vigorous coughing.